Assemblr Edu Based Augmented Reality Flipbook Media to Enhance Critical Thinking Skills of Vocational High School Students: Augmented Reality Flipbook Media - Yuliyanti Yuli; Heni Pujiastuti (Universitas Suryakancana, 2026)
Mathematical critical thinking ability is an essential competency that remains a challenge in Vocational High Schools (SMK). This study aimed to (1) develop a valid and practical Augmented Reality (AR) flipbook media based on Assemblr Edu, and (2) examine its effectiveness integrated with the Problem Based Learning (PBL) model on students' mathematical critical thinking ability. The study employed a Research and Development (R&D) approach using the ADDIE model for media development, and a one-group pretest-posttest quasi-experimental design for effectiveness testing. The sample consisted of 35 Grade XI Electrical Power Installation Engineering (TITL) students selected through simple random sampling. The instrument was a descriptive mathematical critical thinking test declared valid and reliable. Validation by three expert validators in language, content, and media indicated that the media was categorized as highly valid. The practicality test confirmed the media was categorized as highly practical. The effectiveness test demonstrated a significant improvement in students' mathematical critical thinking ability from pretest to posttest, classified in the high category. These findings prove that the Assemblr Edu-based AR flipbook media integrated with the PBL model is significantly effective in improving the mathematical critical thinking ability of SMK students. Keywords: augmented reality Assemblr Edu; mathematical critical thinking; digital flipbook; Problem Based Learning; Vocational High School